2014
DOI: 10.1101/007237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression noise facilitates the evolution of gene regulation

Abstract: Although it is often tacitly assumed that gene regulatory interactions are finely tuned, how accurate gene regulation could evolve from a state without regulation is unclear. Moreover, gene expression noise would seem to impede the evolution of accurate gene regulation, and previous investigations have provided circumstantial evidence that natural selection has acted to lower noise levels. By evolving synthetic Escherichia coli promoters de novo, we here show that, contrary to expectations, promoters exhibit l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 27 publications
7
51
0
Order By: Relevance
“…This fitness cost can be reduced by increased protein fluctuations, i.e. of σ 2 p + α 2 σ 2 s by bet-hedging or 'noisy sensing' strategies, in agreement with previous results [1,2,3]. This can also be shown by differentiating equation 4 with respect to the normalised internal variance and solving for its optimum value, division by ω 2 then gives,…”
Section: The Geometric Fitness Modelsupporting
confidence: 89%
See 2 more Smart Citations
“…This fitness cost can be reduced by increased protein fluctuations, i.e. of σ 2 p + α 2 σ 2 s by bet-hedging or 'noisy sensing' strategies, in agreement with previous results [1,2,3]. This can also be shown by differentiating equation 4 with respect to the normalised internal variance and solving for its optimum value, division by ω 2 then gives,…”
Section: The Geometric Fitness Modelsupporting
confidence: 89%
“…Evolutionary theories about the fitness of phenotypic strategies [1,2,3,4,5,6] have made successful predictions of the outcomes of natural selection in fluctuating environments [3,4,7,8]. In those theories, the (geometric) fitness [4,5,6] is generally maximised.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bull, 1987;Haccou and Iwasa, 1995;Kussell and Leibler, 2005;Tanase-Nicola and ten Wolde, 2008;Ackermann et al , 2008. However, in recent years evidence has been accumulating that gene regulation and gene expression noise may be inherently and intimately linked. For example, several studies have shown that transcriptional noise varies significantly across genes and is to a substantial extent encoded in the promoter sequence of a gene Taniguchi et al , 2010;Silander et al , 2012;Carey et al , 2013;Jones et al , 2014;Wolf et al , 2015. Indeed, whereas genes that are transcribed at a constant rate will exhibit Poissonian fluctuations in mRNA levels, most genes exhibit significantly higher levels of transcriptional noise.…”
Section: Introductionmentioning
confidence: 99%
“…This increased transcriptional noise is generally understood to result, at least partially, from the fact that binding and unbinding of transcription factors (TFs) causes the promoter to stochastically switch between different states that are associated with different transcription initiation rates. In this way, fluctuations in both the expression levels of TFs and their binding to promoter regions are propagated to the their target genes and this noise propagation has long been recognized as an unavoidable side effect of regulation Thattai and van Oudenaarden, 2001;Pedraza, 2005;Lestas et al , 2010;Lehner and Kaneko, 2011;Bruggeman and Teusink, 2018. In a recent study we showed that, in E. coli, unregulated promoters have low expression noise by default, and that the more regulatory inputs a gene has, the more noisy its gene expression tends to be Wolf et al , 2015. A similar general association between highly regulated genes and high expression noise has also been observed in eukaryotes Blake et al , 2003;Newman et al , 2006, and it has also been observed that co-regulated genes show correlated gene expression fluctuations Junker and van Oudenaarden, 2012. All these observations suggest that noise propagation may be a key determinant of gene expression noise.…”
Section: Introductionmentioning
confidence: 99%